18. INVESTIGATE THE VALUE AND CHANGE OF PROCALCITONIN, LACTATE, LEUKOCYTE LEVELS WITH PREDICTIVE FACTORS OF DEATH IN PATIENTS WITH SEPTIC SOHCK AT NGHE AN GENERAL FRIENDSHIP HOSPITAL (Vietnam Journal of Community Medicine, 2023)
Objectives: Investigate the value and change of procalcitonin, lactate, and leukocyte levels with predictive death factors in patients with septic shock.Subjects and methods: Study on 98 patients diagnosed with septic shock treated inpatient and assigned to test procalcitonin, lactate and blood count from 9/2020 to 8/2021.Result: Procalcitonin concentration at time T1 (74.83 ng/mL), the group of survivors was 34.54 ± 22.1 ng/mL and the group of dead was 97.22 ± 41.09 ng/mL; Procalcitonin survival group decreased 33.3% after 24 hours, 62.7% after 48 hours; Procalcitonin mortality group decreased from 1.0% to 0.03% . At the time of T3, the Procalcitonin cut-off value of 35.15 ng/mL (p < 0.01) can predict mortality with a sensitivity of 98.4%; The specificity is 97.1% and the area under the curve is 0.988.Conclusion: Initial procalcitonin levels have a predictive value in mortality in patients with septic shock, and procalcitonin decreases rapidly in patients who respond well to treatment.
Keywords: Procalcitonin; septic shock; Nghe An General Friendship Hospital.